Pemanfaatan Media Kartu Huruf dalam Meningkatkan Pembelajaran Makharijul Huruf Hijaiyah di Tadika Alfikh Orchard Pendamar - Raisa Amanda ZM; Munawir Pasaribu (EduInovasi: Journal of Basic Educational Studies, 2024)
This research was carried out at Tadika Al Fikh Orchard Pendamar, with research subjects being 4 students. The problem that became the urgency for conducting this research was the discovery of problems with students' pronunciation of the hijaiyah letters which were still inaccurate due to a lack of knowledge about the makharijul hijaiyah letters which were in accordance with the rules of recitation science. This research uses a qualitative method with a case study design. This research aims to find out whether the use of letter card media can improve the learning of makharijul hijaiyah letters for 4 students at Tadika Al Fikh Orchard Pendamar. The focus of this research is the hijaiyah letters which are similar but different in terms of makharijul letters. The results of the research show that 4 students at Tadika Al Fikh Orchard Pendamar succeeded in pronouncing the hijaiyah letters correctly after learning the makharijul hijaiyah letters using letter cards, so it can be concluded that the use of letter cards succeeded in increasing the learning of makharijul hijaiyah letters at Tadika Al Fikh Orchard Pendamar.